Conociendo aquello que ocupa un lugar en el espacio - Siancas Zapata, Bertha Cecilia del Pilar (2018)
In daily life, our children know various situations of location, space, shape and others, which lead them to formulate certain questions, among which we can mention why does each body occupy a place in space? Then the need arises to know the context of their development and to face this question in order to give an adequate and real answer that can be understood by our students. The Science and Environment area is the fundamental tool that the teacher uses to explain these situations and does so through research and experimentation. The latter becomes the primary learning tool because when working with reality the child understands and learns quickly. The concepts of matter, space and location are for daily use, children face them at all times and, through practical application, discover new experiences, easily acquire them and adapt them to each moment of their daily life. It is important to understand that the capacities that are put into practice facilitate the integral development of children and their adaptation to the environment where they develop.